DEMOKRASI ESTETIKA DALAM PUISI "SONG OF MYSELF" KARYA WALT WHITMAN - Rujito, Eko (Diksi, 2020)
(Title: Aesthetic Democracy in the Poetry of "Song Of Myself" by Walt Whitman). American poet Walt Whitman is widely considered the father of American modern poetry because of his revolutionary concept of poetry writing. Whitman is a (political) thinker as much as a poet, and most notably, a democratic prophet. Through his abundant essays and poems, he preaches what he refers as aesthetic democracy. Employing descriptive-qualitative method, this paper aims at investigating the application of this concept in Whitman's most famous poem "Song of Myself". The result of the analysis shows that Whitman presents the concept of democracy of aesthetic in the both form and the content of the poem. The form of the poem signifies Whitman's rejection to the old poetic conventions and his aspiration of a more democratic poetic. The content of the poem shows a democratic tendency by involving various themes, subjects and personae with no privilege and subordination towards particular themes, subject or personae.Keywords: aesthetic democracy, Whitman, "Song of Myself"